Evaluasi Pembelajaran PAI Pada Materi Penguatan Aqidah Islam Dalam Membentuk Karakter Siswa Di MTsN 1 Bengkalis - Yuliana Aulia Putri; Murni Sukmawati; Nurfajiani Nurfajiani; Siti Khairiah (Universitas Pakuan, 2026)
Evaluation of PAI Learning on the Material of Strengthening Islamic Aqidah in Shaping Students' Character at MTsN 1 Bengkalis This research is motivated by the importance of evaluating Islamic creed (aqidah) learning enhancement in shaping students’ character, which includes cognitive, affective, and psychomotor aspects. This study aims to describe the implementation of Islamic Religious Education (PAI) learning evaluation on strengthening Islamic aqidah material in shaping students’ character at MTsN 1 Bengkalis and to identify the obstacles faced by teachers. This research uses a qualitative approach with a descriptive type of study. Data were obtained through observations and interviews with teachers and students. The results of this study indicate that learning evaluation was carried out through question-and-answer activities, oral and written tests, attitude observation, and Qur’anic verse memorization practices. The obstacles found include differences in students’ abilities to understand the learning material. To overcome these obstacles, teachers used varied question methods and random questioning techniques so that all students could actively participate in the learning process.